Fifty Years and Learning: Developments in the Roman Catholic Church's Encounter with Religions - Dias, Darren J. (Toronto journal of theology, 2016)
In this article the author argues that the Roman Catholic Church does not have a firm theological position on other religions, as its engagement with them as partners in dialogue has emerged only since the Second Vatican Council. The article provides an overview of the Roman Catholic Church's theology and teachings on non-Christian religions, beginning with the council's shortest, but by no means least-significant, document, Nostra aetate. The author claims that an examination of Nostra aetate's redaction history, the text itself, and the text in relation to other conciliar texts, reveals an optimistic view of salvation and other religions. The author then traces further doctrinal developments in the magisterium of John Paul ii. The length of his papacy, coupled with his personal commitment to dialogue, resulted in significant developments and milestones. The teachings of Benedict xvi and Francis are briefly surveyed. A last section explores ever-evolving theologies and practices that shape the church's approach to other religions today: comparative theology, theologies of dialogue, and theologies of religion.